Immune response to SARS-CoV-2 and review of COVID-19 vaccines - Marković, Miloš (Medicinski podmladak, 2021)
The remarkable development of a large number of vaccines against COVID-19 in a very short period of time represents one of the greatest successes of medicine and science in history, and mass vaccination at the global level will be crucial for prevention and mitigation of COVID-19. However, there are still many open questions about the vaccines, and the protection they provide, and answers to those questions will not only help to control this pandemic, but they will also prepare us to react better in case of future outbreaks. This review will present the latest findings on the immune response to SARS-CoV-2 and give an update on COVID-19 immunity. It will also provide an overview of the most important vaccines against COVID-19, especially those available in Serbia, with an emphasis on their immunogenicity, efficacy and safety, as well as the platforms used for their development. In addition, a special attention will be given to open issues related to immunization against COVID-19, such as the duration of post-vaccination immunity, the degree of protection against new virus variants and the need for booster doses and mixing and matching of different COVID-19 vaccines.
Keywords: COVID-19; SARS-CoV-2; variants; immune response; immunity; vaccines; booster; efficacy; effectiveness; safety.; COVID-19; SARS-CoV-2; variants; immune response; immunity; vaccines; booster; efficiency; effectiveness; safety